Different impact of recovery annealing and thermal pressure treatments on the microstructure and mechanical properties of rejuvenated Cu64Zr36 metallic glasses: a molecular dynamics study - Liu, Rongkang (2024)
The interpenetrating connection of icosahedra network (ICOIN) was termed as structural skeleton, which could quantify the strength and ductility of MGs. The impact of different rejuvenation methods on medium-range order (MRO) alterations was rarely studied. This work employed molecular dynamics simulations to examine the difference in MRO evolution of metallic glasses treated by recovery annealing and thermal-pressure treatment during uniaxial tension. All of the specimens obtain enhanced ductility due to improved potential energy. During tension, ICOI of all rejuvenated specimens exhibits an increased destruction rate and a decreased transformation rate. However, there are some converse characteristics in the specimens under different rejuvenation methods. The rejuvenated specimens treated by recovery annealing exhibit increased free volume and decreased ICOIN density. After thermal-pressure treatment, the rejuvenated specimens demonstrated decreased free volume and enhanced ICOIN density. During tension, the enhancement of icosahedral free volume in specimens treated by thermal pressure largely decreased the ICOIN density, thereby increasing the ductility. After tension, the rejuvenated specimens under high pressure have a significant reduction in ICOIN density compared to those under recovery annealing. The significance of this work is to accurately regulate the ICOIN density of rejuvenated specimens.